Synthesis, characterisation, crystal structure of silver and palladium N-heterocyclic carbene complexes, and investigation of their antimicrobial and catalytic activities - Kaloglu, Nazan; Yapaoz, Melda Altikatoglu; Roisnel, Thierry; Kaloglu, Murat (ELSEVIER, 2026)
In this study, three 1,3-disubstituted imidazolium salts as the N-heterocyclic carbene (NHC) precursors were synthesized. Using these salts, air- and moisture-stable three new silver-NHC complexes, and six new PEPPSI-type (PEPPSI = Pyridine Enhanced Pre-catalyst Preparation Stabilization and Initiation) palladium-NHC complexes were prepared. The structures of all compounds were fully characterized by different spectroscopic and analytical techniques. The more detailed structural characterisation of four of the palladium-NHC complexes was determined by single-crystal X-ray diffraction study. The antimicrobial activities all of the compounds were tested against human pathogenic Gram-positive (S. aureus) and Gram-negative (E. coli) bacterial strains, and fungal strain (A. niger) as potential metallopharmaceutical agents. All synthesized compounds exhibited MIC values ranging from 8 to 128 mu g/mL in antimicrobial assays, thereby confirming their effectiveness as antimicrobial agents against the tested microorganisms. Moreover, all palladium-NHC complexes were employed as catalysts in the direct arylation of nitrogen-containing five-membered heterocyclic compounds such as 3,5-dimethylisoxazole and 1-methyl-1H-pyrrole-2-carboxaldehyde with (hetero)aryl bromides. The desired arylated products were secured in moderate to good yields at 100 degrees C with a 0.5 mol% catalyst loading after just 1 h. Under the tested conditions, (hetero)aryl bromides served successfully as arylating reagents, affording selectively C4arylated isoxazoles and C5-arylated pyrroles in acceptable to high yields.
Keywords: N-heterocyclic carbene; Silver; Palladium; Antimicrobial activity; Direct arylation; NHC COMPLEXES; COORDINATION CHEMISTRY; MEDICINAL APPLICATIONS; METAL-COMPLEXES; ANTICANCER; IMIDAZOLIUM; ANTIBACTERIAL; LIPOPHILICITY; LIGANDS; Chemistry